CORRELATION OF KNOWLEDGE AND COMMUNITY PARTICIPATION IN LAND CONSERVATION-BASED AGROFORESTRY: A CASE STUDY IN TANJUNG AGUNG VILLAGE, LAMPUNG - Kheynad; Christine Wulandari; Eny Puspasari; Pitojo Budiono (Forestry Study Program University Of Mataram, 2025)
The conversion of forest land to agriculture has affected the ecosystem in the upstream area of Way Betung Watershed, including Tanjung Agung Village. This study aims to analyze the relationship between knowledge, community participation, and agroforestry land conservation. The study was conducted on 30 respondents using a structured questionnaire, the results of which were analyzed using the Spearman Rank correlation test. The results showed that the level of community knowledge was in the moderate category (mean score 2.3), while the level of participation was high (mean score 3.7). The level of agroforestry land conservation was recorded in the moderate to high category (mean score 3.3). Correlation analysis showed a significant relationship between knowledge and community participation (ρ = 0.414, p = 0.023) with sufficient closeness, but no significant relationship was found between knowledge and land conservation (ρ = 0.219, p = 0.245) or participation and land conservation (ρ = 0.291, p = 0.119). This study highlights that increasing community participation has great potential to support the success of agroforestry conservation, although the contribution of knowledge needs to be strengthened. The novelty of this research lies in the in-depth analysis of the level of relationship between social variables in supporting agroforestry-based conservation in the strategic upstream area of the Way Betung Watershed.